Author Correction: Whole-genome sequencing provides new insights into genetic mechanisms of tropical adaptation in Nellore (Bos primigenius indicus) (Scientific Reports, (2020), 10, 1, (9412), 10.1038/s41598-020-66272-7) - Fernandes Júnior, Gerardo Alves [UNESP]; de Oliveira, Henrique Nunes [UNESP]; Carvalheiro, Roberto [UNESP]; Cardoso, Diercles Francisco [UNESP]; Fonseca, Larissa Fernanda Simielli [UNESP]; Ventura, Ricardo Vieira; de Albuquerque, Lucia Galvão [UNESP] (Springer Nature, 2021)
The Data Availability section of this Article was incomplete. “The data used in this study were obtained under license and so cannot be publicly available”. now reads: “The data used in this study were obtained under license and so cannot be publicly available. Data are however available from the authors upon reasonable request, and with authorization of Nellore breeding programs”.